Evaluation of the Effectiveness of Team Learning Strategy in the Study of Nomenclature of Organic Compounds among NCE Students - Lamuntani, Dauda Hassan; Yarima, Maryam Magaji (Researchparks Publishing, 2023)
The purpose of this study was to evaluate the effectiveness of team learning strategy in the study of nomenclature of organic compounds among NCE I students. Research objectives, research questions and hypothesis were formulated to guide the researcher in the conduct of the research work. The study used a sample of 20 students out of the population of NCE l chemistry students. The twenty students were randomly placed into experimental and control groups. Experimental-control design was adopted for the study. A pre-test administered to the groups established their equivalent ability. The subjects in the experimental group were treated using team learning strategy and control group was treated using individualistic method for a period of four weeks. The instrument used for data collection was chemistry Achievement Test (CAT) to measure the students’ achievement in chemistry. Independent sample t-test was used to test the hypothesis using SPSS package at 0.05 level of significance. From the T-test result, the probability value (P>0.05) was observed which means there is no significant difference in academic performance among NCE I Students who adopted team learning strategy and those who learned individually. Based on the findings of this research it was recommended that Chemistry teachers in colleges of education in Nigeria should not consider using team learning strategy for teaching as a way of enhancing better understanding of the subject.